Analisis Semiotika Dalam Lirik Lagu Berjudul “One Last Breath” Oleh Creed - Sindi Novianti Putri; Febrian (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the symbolic meanings contained in the lyrics of the song “One Last Breath” by the band Creed using Charles Sanders Peirce’s semiotic theory. The song was selected due to its strong themes of existential crisis, despair, and hope, which are expressed through rich and meaningful linguistic signs. The method used in this research is qualitative descriptive, employing Peirce’s triadic model of signs—icon, index, and symbol—as the basis of data analysis. The primary data source consists of selected lyrics, which were examined to identify the types of signs and their interpreted meanings. The findings reveal that the song's lyrics are filled with emotional symbols reflecting the protagonist's psychological condition, such as the phrase “six feet” as an icon of death, “falling” as an index of mental collapse, and “last breath” as a symbol of the remaining hope. The song also represents Western cultural values related to openness about mental health issues. It is concluded that “One Last Breath” functions not only as a musical work but also as a reflective medium that conveys profound messages about the human struggle and existential meaning. This study is expected to contribute to the development of semiotic analysis in music lyrics and inspire future research on other musical genre.